1984
DOI: 10.1021/bi00296a019
|View full text |Cite
|
Sign up to set email alerts
|

Iminoglycine transport system in synaptosomes and its interaction with enkephalins

Abstract: Evidence is presented which suggests that proline, pipecolic acid, and glycine are accumulated by a common transport system in rat brain cortical synaptosomes and synaptosomal plasma membrane vesicles. This system is Na+ dependent and appears to be similar to the iminoglycine transport system present in renal tubules and in renal brush border membranes. The opioid pentapeptides Leu- and Met-enkephalin specifically inhibit the uptake of these three imino/amino acids, presumably by interaction with a nonopioid r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…The characteristics of the inhibition of vesicular proline uptake by enkephalins were identical qualitatively with those observed with intact synaptosomes (Rhoads et al, 1983b). The inhibition occurred with the enkephalins and des-tyrosylenkephalins but not with morphine or opioid peptides containing the enkephalin peptide sequences.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…The characteristics of the inhibition of vesicular proline uptake by enkephalins were identical qualitatively with those observed with intact synaptosomes (Rhoads et al, 1983b). The inhibition occurred with the enkephalins and des-tyrosylenkephalins but not with morphine or opioid peptides containing the enkephalin peptide sequences.…”
Section: Discussionsupporting
confidence: 69%
“…The properties of the uptake and release of proline in brain slices, synaptosomes, and plasma membrane vesicles derived from synaptosomes are similar to those of known neurotransmitter amino acids (Peterson & Raghupathy, 1972;Bennett et al, 1972;Balcar & Johnston, 1974;Mulder & Snyder, 1974;Balcar et al, 1976;Rhoads et al, 1982a-c). Inhibition of synaptosomal proline uptake by enkephalins was not blocked by the classical opioid antagonist naloxone, and the des-tyrosyl derivatives of the enkephalins inhibited to the same degree as the intact pentapeptides (Rhoads et al, 1983b). These results suggested that the inhibition of proline uptake is due to a nonopioid property of the enkephalins and may, therefore, be mediated by a new subclass of enkephalin receptor, perhaps uniquely coupled to the proline carrier.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…Thus, another potential mechanism for the enhancement of the basal release of Glu and of Asp by tachykinins and CGRP is via the electrogenic transport system, which is Ca2+ independent and would be expected to "release" Glu and Asp whenever cells are depolarized. It is of interest that the Gly uptake system is inhibited by the peptides, leu-and met-enkephalin (Rhoads et al, 1984).…”
Section: Aspmentioning
confidence: 99%